THE IMPLEMENTATION OF SETS INTEGRATED WITH BYOD TO INCREASE STUDENT'S CRITICAL THINKING SKILL ON VIBRATION AND WAVE STUDY - Thoriqi Firdaus; Mochammad Ahied; Nur Qomaria; Dwi Bagus Rendy Astid Putera; Maria Chandra Sutarja (Jurnal Pembelajaran Sains, 2022)
Critical thinking is one of the skills needed to face life's challenges. The SETS learning model is centered on surrounding problems by integrating the four elements of SETS, while BYOD can be used to complete tasks anywhere and anytime. The integration of SETS and BYOD is expected to be able to increase students’ critical thinking skills on vibration and wave study. This study aims to determine the improvement of students' critical thinking skills by implementing the SETS model Integrated with BYOD on vibration and wave study for class VIII SMP. The research method used in this study is a quasi-experimental research design with a nonequivalent control group design which was carried out at SMP Negeri 1 Lenteng, Sumenep Regency, for the 2021/2022 Academic Year. Hypothesis testing using the Mann-Whitney test, and analysis of increased students' critical thinking skills using the N-Gain Score test. The results showed that the implementation of the learning implementation of SETS model Integrated with BYOD was a very good category. The implementation of the SETS model Integrated with BYOD affects student’s critical thinking skills. The increase in students' critical thinking skills based on the N-Gain Score test in the experimental class is a medium category, while the control class is a low category. The results of the student response questionnaire to the implementation of the SETS model Integrated with BYOD are in the good category. This study concludes that the implementation of the SETS model Integrated with BYOD on vibration and wave study can make students increase critical thinking skills.